Stephanus: verleumdet, verehrt, verkannt - Haacker, Klaus (Biblische Gestalten, 2014)
Stephanos Maligned, venerated, misjudged. The account of the fate of Stephen takes up a large part in the Acts of the Apostles. Being the first martyr, Stephen became a Saint and the patron of many churches. There is, however, a modern exegetical tradition which blames Stephen himself for his violent death. Against this, Haaker emphasises the psychological and historical plausibility of Luke s account. The volume reflects the drama of the biblical narrative of Stephen and provides incisive examples of its reception history until the 20th century.